The etiology of severe neonatal hyperbilirubinemia and complications of exchange transfusion - Davutoğlu, Mehmet; Garipardiç, Mesut; Güler, Ekrem; Karabiber, Hamza; Erhan, Deniz (The Turkish Journal of Pediatrics, 2010)
Exchange transfusion (ECT) has an important role in preventing kernicterus in the treatment of indirect hyperbilirubinemia of the newborn. In present study, the etiology of hyperbilirubinemia and complications of ECT were studied over a five-year period in the Eastern Mediterranean region of Turkey. We describe our experience of 89 ECTs performed from 2003-2008 in 79 newborns with hyperbilirubinemia. The mean gestational age was 37 +/- 2.1 weeks and the mean of peak total bilirubin levels was 28.1 +/- 6.4 mg/dl. The most common cause of hyperbilirubinemia was ABO isoimmunization (38%). Complications of ECT developed in 17 neonates (21.5%), the most common being thrombocytopenia and seizure. None of newborns died secondary to ECT. Our data showed higher morbidity rates associated with ECT in the treatment of hyperbilirubinemia in our region. In order to prevent adverse effects of ECT, serum bilirubin levels should be closely monitored in newborns with ABO immunization.